2014
DOI: 10.1016/j.celrep.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Dependent Lon Protease Controls Tumor Bioenergetics by Reprogramming Mitochondrial Activity

Abstract: We generated mice deficient in Lon protease (LONP1), a major enzyme of the mitochondrial quality control machinery. Homozygous deletion of Lonp1 causes early embryonic lethality, whereas its haploinsufficiency protects against colorectal and skin tumors. Furthermore, LONP1 knockdown inhibits cellular proliferation and tumor and metastasis formation, whereas its overexpression increases tumorigenesis. Clinical studies indicate that high levels of LONP1 are a poor prognosis marker in human colorectal cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
245
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(257 citation statements)
references
References 61 publications
11
245
1
Order By: Relevance
“…Deficiency in mouse LONP1 induces alterations in mitochondrial respiration and in the OXPHOS system 39 . Furthermore, homozygous deletion of Lonp1 in mice causes early embryonic lethality, whereas heterozygous mice show decreased tumour susceptibility, which demonstrates the essential role of this proteolytic enzyme in life and disease 39 . In addition to LONP, the mitochondrial matrix contains Ser protease CLPP, which forms the CLPXP complex with the chaperone ATP-dependent Clp protease ATP-binding subunit ClpX-like (CLPX).…”
Section: Protein Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiency in mouse LONP1 induces alterations in mitochondrial respiration and in the OXPHOS system 39 . Furthermore, homozygous deletion of Lonp1 in mice causes early embryonic lethality, whereas heterozygous mice show decreased tumour susceptibility, which demonstrates the essential role of this proteolytic enzyme in life and disease 39 . In addition to LONP, the mitochondrial matrix contains Ser protease CLPP, which forms the CLPXP complex with the chaperone ATP-dependent Clp protease ATP-binding subunit ClpX-like (CLPX).…”
Section: Protein Quality Controlmentioning
confidence: 99%
“…Consistent with the emergence of alterations in metabolism and bioenergetics as hallmarks of cancer 151,152 , recent works have emphasized the functional importance of mitoproteases in various stages of the development and progression of cancer. LONP has a key role in tumour cells, inducing their metabolic reprogramming and protecting them from senescence 39 . Several studies have consistently reported that downregulation of LONP in cancer cells decreases their tumorigenic properties, whereas upregulation protects the cells from various stress conditions and increases their oncogenic potential 39,[153][154][155][156][157][158] .…”
Section: Mitoproteases and Human Diseasesmentioning
confidence: 99%
“…In mouse colorectal cancer cells and a skin tumor model, knocking down LONP1 reduced the OxPhos and inhibited tumor formation. In human colon cancers, upregulation of LONP1 was associated with increased tumor growth and a poor survival rate (Quiros et al 2014). Clinically, these observations convey significant implications for the development cancer therapeutics that target tumor bioenergetics as an indispensable ''adjuvant'' which allows oncogenic pathway inhibitors to preemptively eradicate CSCs.…”
Section: Metabolic Transition During Reprogramming Of Nonstem-like Camentioning
confidence: 99%
“…By doing so, DLD1‐miR661 cells maintain high levels of membrane potential, which also contributes to the use of TCA intermediates for biosynthesis instead of oxidative phosphorylation. This is in agreement with the decreased levels of BRR and MRR that reflect a reduced catabolism to preserve anabolism, a mechanism of adaptation already described for LONP1‐overexpressing cells (Quirós et al ., 2014). In summary, these results reflect a miR661‐dependent metabolic reprogramming affecting both glycolysis and mitochondrial respiration to preserve anabolic processes (mitochondrial anabolic mode).…”
Section: Resultsmentioning
confidence: 99%